Relationships between Maternal Copper and Iron Serum Levels with Pregnancy Outcomes and Relationship between their Maternal and Cord Levels - Elahe Seddighi Looye; Lida Moghaddam Banaem; Azam Afshar (Tehran University of Medical Sciences, 2011)
Background & Aim: This study aimed to assess the relationships between iron and copper levels in maternal and cord serums together and with pregnancy outcomes. Methods & Materials: An Analytical cross-sectional study was conducted among 370 pregnant women in labor and their neonates in Maryam, Akbarabadi and Imam hospitals in Tehran, Iran. Copper concentrations were measured using the standard atomic absorption spectrophotometer method and Iron concentrations were measured by a kit through RA 1000 method. Data were collected using a questionnaire and were analyzed using Spearman correlation, Chi- square and Logistic regression tests. Results: The mean copper concentrations in the maternal and cord bloods at delivery were 114.52±37.4, 22.4±11.6 (μg/dl), respectively. The Iron levels were 119.2±64, 164.3±65.3 (μg/dl), respectively. Of all the mothers, 54.3% had copper deficiency, 1.1% Iron deficiency and of all the newborns, 44.7% had copper deficiency and 3.5% Iron deficiency. The Spearman Correlation analysis showed significant positive correlations between concentrations of each element in maternal serum with cord serum and also between maternal iron with maternal copper, and maternal iron with cord copper. The Chi-square analysis showed that there was a significant relationship between maternal copper deficiency and gestational hypertension (P<0.001). There were no significant relationships between these trace element levels at delivery with premature rupture of membranes and preterm labor. Logistic regression analysis showed a significant negative relationship between maternal copper levels and gestational hypertension (odds: 0.98, 95%CI: 0.97-0.99). Conclusion: Maternal copper deficiency was rather high in the participants of the study (54.3%), and was related to incidence of gestational hypertension. These findings illustrated importance of trace elements during pregnancy. Providing suitable dietary recommendations and giving supplements during pregnancy can help to decrease maternal and fetal mortality and morbidity.